Hypotrichous ciliates (Protozoa: Ciliophora) from a temporary pond in Argentina, with redescription of Apoamphisiella hymenophora (Stokes, 1886) Berger, 1999 - Küppers, Gabriela C.; Claps, María C. (Zootaxa, 2013)
Hypotrichous ciliates collected in the plankton and soil samples from a temporary pond in Buenos Aires province, Argen-tina, were characterized after live observations and protargol impregnation. Apoamphisiella hymenophora (Stokes) Berger is redescribed and the neotype material deposited. Apoamphisiella hymenophora differs from its congeners in having 2 macronuclear nodules, 1 contractile vacuole with anterior and posterior collecting canals, the absence of cortical granules, 2 cirri behind the rightmost frontal cirrus, 1 postoral cirrus, 6 dorsal rows of dikinetids along with scattered dikinetids on the right body margin, and 3–9 caudal cirri arranged in groups at the ends of dorsal rows 1, 2, and 4. Rigidohymena can-dens, R. quadrinucleata, Histriculus histrio, Gastrostyla steinii, and Pseudouroleptus caudatus are new for the Argentine microfauna. Since especially the soil ciliates have been almost unexplored in South America, the results from the present investigation describe and contribute to the knowledge of the diversity of these microorganisms within this geographical region.